Regional variability in land and water use in fruit and vegetable production in the United States. Issue 1 (13th December 2021) - McCarthy, Ashley C.; Griffin, Timothy S.; Srinivasan, Sumeeta; Peters, Christian J.
Abstract: Public concern about the environmental consequences of our diets is growing and regional food systems have emerged as one strategy to reduce these impacts. However, the potential environmental benefits of regional food systems are still largely untested and more empirical evidence is needed. Land and water are critical inputs to agriculture, but natural resource requirements and associated environmental impacts are highly dependent crop production location. This study used statistical analyses of crop yield and water footprint data to examine regional variability in land and water requirements and location‐specific tradeoffs between these resources. Regional land requirements and water requirements differed among most of the 17 fruit and vegetable crops we examined. Our results also showed inverse relationships between land and irrigation water requirements for eight crops, indicating that location‐specific tradeoffs between land and water resources exist for these crops. Understanding these regional differences and tradeoffs in natural resource requirements can help us evaluate the environmental implications of a more regionalized food system. Core Ideas: Land and irrigation water requirements of 17 fruit and vegetable crops were analyzed. Regional land requirements vary significantly for all crops. Regional water requirements vary significantly for all crops, except snap beans. Location‐specific tradeoffs between land and water requirements exist for eight crops. These findings can help us evaluate the environmental impacts of regionalized food systems.